(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This study explores the concept of linguistic variables within the field of regional dialectology, focusing on how language varies across geographical areas. Linguistic variables—features of pronunciation, grammar, and vocabulary—are key to identifying and analyzing regional dialects. This article examines the methods used in collecting and analyzing dialectal data, the patterns that emerge from such analysis, and the implications for understanding linguistic diversity, identity, and change. The research highlights the value of dialect studies in preserving linguistic heritage and informing sociolinguistic theory.